Exploring the most visible german websites on melanoma immunotherapy: A web-based analysis - Bruetting, Julia; Steeb, Theresa; Reinhardt, Lydia; Berking, Carola; Meier, Friedegund (JMIR Cancer, 2018)
Background: Patients diagnosed with melanoma frequently search the internet for treatment information, including novel and complex immunotherapy. However, health literacy is limited among half of the German population, and no assessment of websites on melanoma treatment has been performed so far. Objective: The aim of this study was to identify and assess the most visible websites in German language on melanoma immunotherapy. Methods: In accordance with the common Web-based information-seeking behavior of patients with cancer, the first 20 hits on Google, Yahoo, and Bing were searched for combinations of German synonyms for "melanoma" and "immunotherapy" in July 2017. Websites that met our predefined eligibility criteria were considered for assessment. Three reviewers independently assessed their quality by using the established DISCERN tool and by checking the presence of quality certification. Usability and reliability were evaluated by the LIDA tool and understandability by the Patient Education Materials Assessment Tool (PEMAT). The Flesch Reading Ease Score (FRES) was calculated to estimate the readability. The ALEXA and SISTRIX tools were used to investigate the websites' popularity and visibility. The interrater agreement was determined by calculating Cronbach alpha. Subgroup differences were identified by t test, U test, or one-way analysis of variance. Results: Of 480 hits, 45 single websites from 30 domains were assessed. Only 2 website domains displayed a German quality certification. The average assessment scores, mean (SD), were as follows: DISCERN, 48 (7.6); LIDA (usability), 40 (2.0); LIDA (reliability), 10 (1.6); PEMAT, 69% (16%); and FRES, 17 (14), indicating mediocre quality, good usability, and understandability but low reliability and an even very low readability of the included individual websites. SISTRIX scores ranged from 0 to 6872 and ALEXA scores ranged from 17 to 192,675, indicating heterogeneity of the visibility and popularity of German website domains providing information on melanoma immunotherapy. Conclusions: Optimization of the most accessible German websites on melanoma immunotherapy is desirable. Especially, simplification of the readability of information and further adaption to reliability criteria are required to support the education of patients with melanoma and laypersons, and to enhance transparency.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Immunotherapy; Information; Internet; Melanoma; Patient education; Quality; Readability; Reliability; Websites